Deep Disagreement and the Virtues of Argumentative and Epistemic Incapacity - Barris, Jeremy (Informal Logic, 2018)
Fogelin’s (1985) Wittgensteinian view of deep disagreement as allowing no rational resolution has been criticized from both argumentation theoretic and epistemological perspectives. These criticisms typically do not recognize how his point applies to the very argumentative resources on which they rely. Additionally, more extremely than Fogelin himself argues, the conditions of deep disagreement make each position literally unintelligible to the other, again disallowing rational resolution. In turn, however, this failure of sense is so extreme that it partly cancels its own meaning as a failure of sense. Consequently, it paradoxically opens new possibilities for sense and therefore rationally unexpected resolutions.